„L’ uomo nuovo” nei testi di Virginie Despentes e Sandro Veronesi - Magdalena Lange-Henszke (Studia Paradyskie)
The utopian myth of the new man is a concept present in all eras. Religion, philosophy, politics, literature, art, science perceive the new man as a perfect individual, a hero or a charismatic leader of a new humanity, liberated from all evil. In the second half of the 19th century, the revolutionary concept of individual freedom is transformed into a collective vision, the vision of a dominant race composed of "ordinary" people united by a common experience. The issue of subjectivity regains fundamental importance for humanistic thought in the second half of the 20th century, among others, thanks to the reflections proposed by feminist theory. Third-wave feminism highlighted the problem of intersectionality and detachment from women's real, everyday problems, but also proposed strategies for possible changes for men. Theorists and writers such as bell hooks and Virginie Despentes argue that men can regain the areas from which patriarchy pushed them - self-knowledge, contact with their own feelings, involvement in practices of care. Virginie Despentes in her essay King Kong Theory points out that patriarchy is a political system that affects all members of society. Men demonstrate a profound misunderstanding of this central aspect that gives form and content to their identity and forces them to behave in a certain way, regardless of their personality needs. Virginie Despentes in The King Kong Theory and Sandro Veronesi in the novel Il Colibrì, using different methodologies, diagnose the same problems and propose similar solutions, attempting to outline the profile of the "new man". They postulate a new social order based on the needs and predispositions of the individual, not subject to the requirements of gender performance. Veronesi places the practice of care at the center of his narrative as a key element of the new masculinity. The "new man" appears as an androgynous being, able to combine care for others with the principle of pleasure.